Polarized Signatures of the Earth Through Time: An Outlook for the Habitable Worlds Observatory - Kenneth E. Goodis Gordon; Theodora Karalidi; Kimberly M. Bott; Nicholas F. Wogan; Giada N. Arney; Mary N. Parenteau; Tiffany Kataria; Victoria S. Meadows (The Astrophysical Journal)
The search for life beyond the solar system remains a primary goal of current and near-future missions, including NASA’s upcoming Habitable Worlds Observatory (HWO). However, research into determining the habitability of terrestrial exoplanets has been primarily focused on comparisons to modern-day Earth. Additionally, current characterization strategies focus on the unpolarized flux from these worlds, taking into account only a fraction of the informational content of the reflected light. Better understanding the changes in the reflected-light spectrum of the Earth throughout its evolution, as well as analyzing its polarization, will be crucial for mapping its habitability and providing comparison templates to potentially habitable exoplanets. Here we present spectropolarimetric models of the reflected light from the Earth at six epochs across all four geologic eons. We find that the changing surface albedos and atmospheric gas concentrations across the different epochs allow the habitable and nonhabitable scenarios to be distinguished, and diagnostic features of clouds and hazes are more noticeable in the polarized signals. We also discuss how using Mie scattering for naturally nonspherical particles, which is a common simplification for exoplanet modeling, affects the resulting planetary signals. Finally, our results suggest that pushing the HWO planet-to-star flux contrast limit down to 1 × 10 ^−13 could allow for the characterization in both unpolarized and polarized light of an Earth-like planet at any stage in its history.